2017
DOI: 10.5588/ijtld.17.0060
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pulmonary aspergillosis as a cause of smear-negative TB and/or TB treatment failure in Nigerians

Abstract: CPA is a neglected disease in Nigeria, and most cases match the World Health Organization diagnostic criteria for smear-negative TB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
121
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(127 citation statements)
references
References 7 publications
4
121
2
Order By: Relevance
“…This definition is consistent with the original definition of CPA proposed by Denning and colleagues [1]. Still, CPA is under-and mis-diagnosed in resource-constrained settings where adequate diagnostics are unavailable [6]. Previously treated PTB is the most common risk factor for the development of CPA even in the developed world [1].…”
supporting
confidence: 78%
See 1 more Smart Citation
“…This definition is consistent with the original definition of CPA proposed by Denning and colleagues [1]. Still, CPA is under-and mis-diagnosed in resource-constrained settings where adequate diagnostics are unavailable [6]. Previously treated PTB is the most common risk factor for the development of CPA even in the developed world [1].…”
supporting
confidence: 78%
“…The global burden of CPA attributed to healed TB lesions alone has been estimated to over 1.2 million cases annually globally [7]. On the other hand, active PTB is the number one differential diagnosis for CPA and CPA is the number one differential diagnosis for patients previously treated for microbiologically confirmed PTB who are currently sputum smear-negative [6]. Recent evidence has shown that the annual rate of new CPA development following completion of PTB treatment is about 6.5% in those with chest radiography cavitation and 0.2% in those without [8] (Fig.…”
mentioning
confidence: 99%
“…Several studies have recently been published with serological data using only commercial ELISA tests for CPA diagnosis in an area with high tuberculosis prevalence [1,12,37].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have recently been published with serological data using only commercial ELISA tests for CPA diagnosis in an area with a high prevalence of tuberculosis [1, 13, 36].…”
Section: Discussionmentioning
confidence: 99%